2012
DOI: 10.1073/pnas.1201398109
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of a putative metal permease in Chlamydia trachomatis yields an iron-dependent transcriptional repressor

Abstract: The regulation of iron homeostasis is essential for most organisms, because iron is required for a variety of conserved biochemical processes, yet can be toxic at high concentrations. Upon experiencing iron starvation in vitro, the obligate intracellular human pathogen Chlamydia trachomatis exhibits elevated expression of a putative iron-transport system encoded by the ytg operon. The third component of the ytg operon, CT069 (YtgCR), encodes a protein with two distinct domains: a membrane-anchored metal ion pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…We then sequenced the 478 ligated inserts and BLASTed the sequences against the C. trachomatis L2 434/Bu 479 genome to identify the location of the 5'-most nucleotides ( Figure 4C). These data are 480 displayed as a statistical approximation of the genomic regions most likely to be 481 galactosidase activity (p = 0.03868) consistent with its previously reported auto-588 regulation of this promoter (Thompson et al, 2012). 589…”
Section: Limitation 352supporting
confidence: 79%
See 2 more Smart Citations
“…We then sequenced the 478 ligated inserts and BLASTed the sequences against the C. trachomatis L2 434/Bu 479 genome to identify the location of the 5'-most nucleotides ( Figure 4C). These data are 480 displayed as a statistical approximation of the genomic regions most likely to be 481 galactosidase activity (p = 0.03868) consistent with its previously reported auto-588 regulation of this promoter (Thompson et al, 2012). 589…”
Section: Limitation 352supporting
confidence: 79%
“…Importantly, Chlamydia presumably acquire iron via vesicular 127 interactions between the chlamydial inclusion and slow-recycling transferrin (Tf)-128 containing endosomes (Ouellette & Carabeo, 2010). IFN-g is known to down-regulate 129 transferrin receptor (TfR) expression in both monocytes and epithelial cells with 130 YtgC (CTL0325) open reading frame (ORF) encodes a N-terminal permease domain 138 fused to a C-terminal DtxR-like repressor domain, annotated YtgR (Akers,HoDac,139 Lathrop, & Tan, 2011; Thompson, Nicod, Malcolm, Grieshaber, & Carabeo, 2012). YtgR 140 is cleaved from the permease domain during infection and functions as an iron-141 dependent transcriptional repressor to autoregulate the expression of its own operon 142 (Thompson et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the precise physiological role of T. pallidum TroA remains unclear, while it has been implicated in potentially mediating Mn 2+ , Fe 2+ and/or Zn 2+ uptake (Desrosiers et al 2007; Hazlett et al 2003). Similarly, YtgA from Chlamydia trachomatis has been associated with Fe 2+ , Fe 3+ and/or Zn 2+ transport processes, although a direct physiological role has not been shown (Akers et al 2011; Miller et al 2009; Thompson et al 2012). One of the very few functional roles that have been definitively established within this subgroup is for TroA from S. suis and its role in physiological Mn 2+ acquisition (Wichgers Schreur et al 2011).…”
Section: Structure Function and Metal Specificity Of Cluster A-i Sbpsmentioning
confidence: 99%
“…Close homologs of DtxR are widely distributed among Corynebacterium spp. (Oram et al 2004;Brune et al 2006), and more distantly related homologs of DtxR have been identified in numerous bacterial genera (particularly among Gram-positive and acid-fast bacteria), including but not limited to: Brevibacterium lactofermentum (Oguiza et al 1995), Chlamydia trachomatis (Thompson et al 2012), Mycobacterium smegmatis (Dussurget et al 1996), Mycobacterium tuberculosis , Staphylococcus aureus (Hill et al 1998), Staphylococcus epidermidis (Hill et al 1998), Streptomyces lividans (Gunter-Seeboth and Schupp 1995), Streptomyces pilosus (Gunter-Seeboth and Schupp 1995), and Treponema pallidum (Hardham et al 1997). The iron-dependent regulator (IdeR) from M. tuberculosis was the first member of the DtxR family shown to be a dual regulator that can repress transcription at some promoters that it regulates and activate transcription at other promoters that it regulates (Gold et al 2001).…”
Section: Regulation Of Diphtheria Toxin Productionmentioning
confidence: 97%